POLA PERMUKIMAN PESISIR PANTAI Studi Kasus: Desa Talaga 1 dan Desa Talaga 2 Kecamatan Talaga Raya Kabupaten Buton Tengah - Sarman, Sufrin; Wijaya, Karto (Jurnal Arsitektur ZONASI, 2018)
The pattern of fish settlements in this region is an island located in Southeast Sulawesi. This study aims to determine the environmental patterns of fishermen settlements in Talaga Kelurahan and Talaga two subdistricts Talaga Raya Central Buton District Southeast Sulawesi. Analysis of electricity village and village Talaga two subdistricts Talaga Raya Central Buton regency of Southeast Sulawesi, lift berdasar from the data in the settlement. Analytical techniques used are qualitative analysis and analysis and analysis of data source of settlement environment pattern in Talaga Satu and Talaga Dua Village, Talaga Raya Sub-district, Central Buton Regency of Southeast Sulawesi. Evacuation on islands and villages in Talaga village one and the condition of poles of fishermen settlement in the village in Talaga Village two.